Intersections between heritage, multilingualism, and education: language acquisition in India - Sarma, Vaijayanthi M. (Frontiers in Human Neuroscience, 2025)
India is a profoundly diverse nation-state where constitutional provisions for two official and 22 Scheduled languages overlay a vast substratum of numerous Non-Scheduled languages and over a thousand distinct mother tongues, creating a rich and layered linguistic hierarchy. The trajectory of linguistic growth of young Indians is invariably multilingual and multidialectal and involves at least one L1, followed most often by Hindi and English or other languages. We carried out a qualitative study with over over a thousand students entering university using a modified LEAP questionnaire for self-assessment of fluency, literacy, domain of use, and time course of language acquisition and loss. We explore the interaction between heritage language, multilingualism, and the formal (trilingual) education policy and show that they intersect to redraw the linguistic profiles of individuals with shifting language dominance, and impact linguistic ability, especially in L1. We also find that the understanding of “heritage language” needs to be more nuanced in this particular context of multilingualism and language acquisition.